Pendampingan Keterampilan Desain Grafis dan Multimedia bagi Siswa SMP Negeri 04 Kota Lubuklinggau melalui Aplikasi Canva - Marsehan, Ahmad; Nopalia, Nopalia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This Community Service (PKM) aims to improve the graphic design and multimedia skills of SMP Negeri 04 Lubuklinggau City students through the application of Canva application as a companion tool. The Community Service method used is a step that has been planned with the following steps which include: planning, implementation, observation, and reflection. The results of the community service showed a significant improvement in students' graphic design and multimedia skills after the application of assistance using the Canva application. Students showed improved understanding of graphic design concepts, ability to integrate multimedia elements, and creativity in presenting information. In addition, student participation and interest in learning also increased during the learning process. Assistance using the Canva application proved effective as an innovative method in improving students' skills in graphic design and multimedia. The implications of this community service show that the utilization of technology in learning can have a positive impact on the development of students' skills in the digital era. This community service contributes to the literature of innovative learning and provides recommendations for schools and teachers to integrate technology in the learning process of graphic design and multimedia at the junior high school level.